An Evening with Anri Kulev’s Films - Popova, Nevelina (Sledva : NBU Journal of Humanities and Arts, 2019)
A celebration of Anri Kulev’s films at the New Bulgarian University is just a starting point for a broader overview of the work of this significant Bulgarian artist, cartoonist and film director